Polyphony as Political Exercise: Reading Retelling of Epic Characters (Journal of Pharmaceutical Negative Results, 2022)
Attempts have been made in retelling Epics Ramayana and Mahabharata from the very inception of these works. Both epics are a reflection of Indian society. The retelling of epics also implies a political analysis and cultural analysis of the nation. The fascinating things about the retelling are that they give voices to the silenced characters, echoes the suppressed voices of the marginalised and peripheral people. Such reading of fiction based on the Epics invites us to engage in the politics of the text. The diversity of the voices found in the novels reminds the reader of the theories of Bakhtin. Each voice is valid, according to Bakhtin. While reading the retelling of Epic Characters, the reader finds the silenced men and women in the original text have found their voices in the present retelling. Bakhtinian theory of polyphony and heteroglossia can be used to analyse the politics of the past and present. Therefore this paper proposes polyphony as means of the socio-political analysis of the retelling of epics.